Changes in muscle activity with increasing running speed - Kyröläinen, H.; Avela, J.; Komi, P. V. (Journal of Sports Sciences, 2005)
Electromyographic (EMG) activity of the leg muscles and the ground reaction forces were recorded in 17 elite male middle-distance runners, who performed isometric maximal voluntary contractions (MVC) as well as running at different speeds. Electromyograms were recorded from the gluteus maximus, vastus lateralis, biceps femoris, gastrocnemius and tibialis anterior. The results indicated that the averaged EMG (aEMG) activities of all the muscles studied increased (P < 0.05) with increasing running speed, especially in the pre-contact and braking phases. At higher speeds, the aEMG activities of the gastrocnemius, vastus lateralis, biceps femoris and gluteus maximus exceeded 100% MVC in these same phases. These results suggest that maximal voluntary contractions cannot be used as an indicator of the full activation potential of human skeletal muscle. Furthermore, the present results suggest that increased pre-contact EMG potentiates the functional role of stretch reflexes, which subsequently increases tendomuscular stiffness and enhances force production in the braking and/or propulsive phases in running. Furthermore, a more powerful force production in the optimal direction for increasing running speed effectively requires increased EMG activity of the two-joint muscles (biceps femoris, rectus femoris and gastrocnemius) during the entire running cycle.